2017
DOI: 10.1186/s13104-017-2748-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of standard precautions and barriers to compliance among healthcare workers in the Lower Manya Krobo District, Ghana

Abstract: BackgroundImplementing standard precautions (SP) has been a major challenge for health care workers (HCWs) especially those in developing countries thereby compromising their safety and increasing their exposure to blood-related pathogens. Compliance with safety precautions and occupational accidents among health workers are often unreported. The literature on knowledge and compliance to SP in Ghana is scanty. We report findings of a study that examined knowledge of SP, compliance and barriers to compliance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 46 publications
9
41
6
1
Order By: Relevance
“…This is in agreement with Zhang et al [12] who opined that HCWs lack knowledge about blood borne pathogens (BBPs) transmission and SPs in China. Also HCWs was reported to have low level of knowledge of SPs in Ghana [10]. HCWs are not continually informed on SPs principles, insufficiencies or lack of knowledge and practice of SPs [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with Zhang et al [12] who opined that HCWs lack knowledge about blood borne pathogens (BBPs) transmission and SPs in China. Also HCWs was reported to have low level of knowledge of SPs in Ghana [10]. HCWs are not continually informed on SPs principles, insufficiencies or lack of knowledge and practice of SPs [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…39.0% of the HCWs recognized cough protocols and only 40.0% knew about sanitary procedures which comprise infection preventive approaches to curb the dangers of exposure to infection. Fifty percent of the HCWs continually protect themselves against blood and body fluids (BBFs) of patients, 25% do not recap needles after usage and 28.0% do not always wipe blood spills on time [10]. Sixty-three percent of HCWs opined that using PPEs such as aprons, gloves, gowns and goggles, might cause patients to fright occasionally and adhering to SPs sometimes obstructs the ability to offer care (38.0%).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of supervision from nurses who are more experienced in work can cause injury in the implementation of injection practices (Gershon et al, 2007). This is supported by research conducted by Akagbo et al, (2017) which shows that only 17% of respondents use eye protection, 34% reuse needles that have been used and always report the incidence of needle stick injuries. The incidence of needle syringe often causes major injury due to work and exposure to harmful bacteria and infections among health workers.…”
Section: The Biggest Barriers Perceived By Nurses On Safe Injection Pmentioning
confidence: 75%
“…The same barriers were found in many studies. Most of the respondents (74%) reported the absence or insufficiency of tools such as masks, gloves, and protective goggles to be the main barriers to compliance in implementing precautions (Akagbo et al, 2017). One study in Malaysia reported that 44% of nurses stated that gloves were not available especially in emergency situations (Naing et al, 2001).…”
Section: The Biggest Barriers Perceived By Nurses On the Use Of Ppe Imentioning
confidence: 99%
See 1 more Smart Citation